Upaya Peningkatan Aktivitas Diskusi Pada Pembelajaran Sejarah Dengan Menggunakan Model Pembelajaran Cooperative Tipe Make A Match - Siti Aminah; Ridho Bayu Yefterson (Jurusan Sejarah FIS UNP, 2021)
This research is motivated by the lack of teacher innovation in using learning models so that it causes a lack of cstudent activity in group discussion in class on history subjects, especially in class XI IPS 3 at SMA Negeri 8 Padang. The purpose of this research is to increase student activity in group discussion on history subject by applying the Cooperative Learning type Make A Match model to students of class XI IPS 3 at SMA Negeri 8 Padang. The method used in this research is Classroom Action Research (CAR). Data is collected by using observations, interviews, documentation and field notes. The percentage of student activeness in group discussion increased in the first cycle 66,74% and in the second cycle increased to 84,21%. From these result it can be concluded that the application of the Cooperative Learning type Make A Match model can increase student activity in group discussion on history subjects in class XI IPS 3 SMA Negeri 8 Padang.